2019
DOI: 10.1002/adfm.201904356
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Limitations to Meet Highly Stable Bio‐Hybrid Light‐Emitting Diodes

Abstract: Color down-converting filters with fluorescent proteins (FPs) embedded in a polymer matrix have led to new bio-hybrid light-emitting diodes (Bio-HLEDs), featuring stabilities of 100 h and <1 min at low and high applied currents, respectively. Herein, the FP deactivation mechanism in Bio-HLEDs at high driving currents is deciphered. Primarily, the nonradiative energy relaxation of FPs upon excitation promotes the release of excess energy to the polymer matrix, reaching 60 °C and, in turn, a significant thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 74 publications
(88 reference statements)
3
54
0
Order By: Relevance
“…8). Note, also that previous Bio-HLEDs based on elastomeric filters with eGFP featured efficiencies of 27 lm/W and L 50 of 2 min at the same driving conditions 31 . This highlights the prospect of the mutant regardless of the chosen polymer matrices.…”
Section: Fluorescent Protein Designmentioning
confidence: 82%
See 4 more Smart Citations
“…8). Note, also that previous Bio-HLEDs based on elastomeric filters with eGFP featured efficiencies of 27 lm/W and L 50 of 2 min at the same driving conditions 31 . This highlights the prospect of the mutant regardless of the chosen polymer matrices.…”
Section: Fluorescent Protein Designmentioning
confidence: 82%
“…These approaches rely, however, on chemical modifications of PMMA and chemical reactions with the biocompounds, risking the stability and optical features of the final materials. To circumvent these issues, we have shown that the hydrophilic TMPE polymer significantly stabilizes FPs in gel and elastomeric forms with a high content of water under storage and device operating conditions 15,27,30,31 . Now, we state that this approach can also be applied to stabilize FPs in very dry media, shielding the surrounding of the FP structure against the toxic polymer solution environment for long periods of time (Fig.…”
Section: Fluorescent Protein Designmentioning
confidence: 99%
See 3 more Smart Citations